ANALISIS IMPLEMENTASI PROGRAM E- KTP DI KOTA SEMARANG - Pentury, Luther Aprinando; Rengga, Aloysius; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The event is one of the aspects of residency in a country which is very important and has influence because it is concerned about his life. The Government based on Pancasila and the Constitution of 1945 on the fact that the obligation to provide protection and recognition of personal status and the determination of the legal status of any event on population and Vital Events experienced by the entire population of Indonesia. To provide protection, recognition, personal status and the determination of the legal status of any event on population and Vital Events experienced by the entire population needs to be done about the residency Administration settings.Based on the above, this study will throw light on how the implementation of the E-ID CARD Program in the city of Semarang last with based on the applicable regulation in realizing the orderly administration of the settlement. This research uses theories by observing the criteria of correctness of implementation policies, implementing elements of accuracy, precision, and accuracy of the target environment. Research method used through observation, interviews, documentation, and libraries with the studies service of the employee population and informant civil registration Semarang.The results showed the Program implementation of the E-ID CARDS in Semarang City based on four criteria in reaching effective implementation, not entirely right. As for the aspects that support the implementation of this Program in realizing the orderly administration of the residency is clarity of policy set by the Government in realizing the significance of the Act Number 23 / 2006. While the Barriers were found there on implementing aspects of the policy that lead to a better quality of human resources, the target implementation, environment as well as public participation is minimal.Â In overcoming obstacles that there have been some suggestions that can be made as needed socialization and understanding about the meaning of an intensive and content policies that have been set, maturation in the phases of activity planning, implementation, and supervision so that activities run in accordance with the path, improvements in terms of the disposition and the bureaucratic structure, mentoring and group adjustments with the prevailing culture in the area.